Cross Cloud Computing in Security System - Gupta, Ankur; garg, Puneet (IJRDO -Journal of Computer Science Engineering, 2017)
Cloud Computing has been information technologies services on developed to deliver demand to organizations like asindividual users, this technology is still in its early stages of development because it suffers from different security threats that preventusers trust it In this paper, we identify different security problems existing in cloud from several research papers & we show suggestedsolutions. This cross cloud represents next logical wave in computing, enabling complex hybrid applications, cost & performanceoptimization, enhanced reliability, customer flexibility & lock-in avoidance. Providing testing as a service in cross clouds become hottopics in industry.